What is the optimum rehabilitation for patients who have undergone release procedures for frozen shoulder? A UK survey. (April 2021) - Willmore, Elaine; McRobert, Cliona; Foy, Chris; Stratton, Irene; van der Windt, Danielle
Abstract: Objective: Despite usually being considered necessary, the rehabilitation regime that optimises outcomes for patients following release procedures for frozen shoulder has not been established and no accepted best practice guidelines currently exist. The purpose of this study was to gain insight into what physiotherapists considered best practice and factors they considered likely to affect patient outcome. Methods: A cross-sectional, self-administered online questionnaire was developed and distributed to UK based Physiotherapists, undergraduate students and support workers via email, social media and professional networks. Results: 260 eligible and fully completed surveys were received. Clear preference for early (within 72 h), frequent (2–3 times per week or weekly) and prolonged (greater than 6 weeks) treatment delivered in a 1:1 setting was expressed. 99% were highly likely/likely to advocate education and advice, range of movement exercises (99.6%), stretching (73.5%) and strengthening (61.9%). More passive modalities (manual therapy, massage, electrotherapy, acupuncture) were highly unlikely/unlikely to be used and lack of manual therapy and insufficient contact with a physiotherapist were the reasons deemed least likely to affect outcome. Most clinicians (89.2%) were likely to prescribe exercises that patients reported as painful but persistent pain and poor adherence by patients to exercises were the top reasons given for poor outcome along with psychological and psychosocial patient characteristics. Conclusion: Physiotherapists consistently advocate early, frequent, prolonged, 1:1 treatment following release procedures for frozen shoulder. Most patients are discharged whilst still experiencing symptoms, particularly pain. Further work is needed to establish high value pathways for this patient group. Highlights: Optimal rehabilitation following release procedures for frozen shoulder is unknown. Physiotherapists prefer early, frequent, prolonged, 1:1 treatment. This appears to be based on clinician preference rather than high quality evidence. Most physiotherapist expect patients to still have symptoms when discharged. Further work to develop high value clinical guidelines for this group is required.